2020
DOI: 10.29374/2527-2179.bjvm107420
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus pseudintermedius: an underestimated risk at pet clinic

Abstract: The prevalence of methicillin-resistant Staphylococcus pseudintermedius (MRSP) as a cause of infectious disease in companion animals remains unknown. The emergence of MRSP is a challenge in veterinary medicine as multidrug-resistant strains began to emerge, resulting in treatment failures. This study provides an overview of the characterization of S. pseudintermedius strains from clinical pet samples and the prevalence of MRSP strains. A total of 123 S. pseudintermedius strains were characterized by phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…We have shown that four canine strains of S. pseudintermedius obtained from the University Veterinary Teaching Hospital in Naples, Italy, had multidrug resistance (MDR) profiles, being resistant to antimicrobial agents that are frequently prescribed for dogs with both MRSP and MSSP infections. Our findings are consistent with those of others, showing the broad, worldwide, increasing prevalence of antimicrobial-resistant S. pseudintermedius strains in dogs [17][18][19]. In addition, MSSP strains have shown increased resistance to most of the antimicrobials currently licensed for use in pets [3,4,[20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that four canine strains of S. pseudintermedius obtained from the University Veterinary Teaching Hospital in Naples, Italy, had multidrug resistance (MDR) profiles, being resistant to antimicrobial agents that are frequently prescribed for dogs with both MRSP and MSSP infections. Our findings are consistent with those of others, showing the broad, worldwide, increasing prevalence of antimicrobial-resistant S. pseudintermedius strains in dogs [17][18][19]. In addition, MSSP strains have shown increased resistance to most of the antimicrobials currently licensed for use in pets [3,4,[20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of antibiotic multiresistant bacteria is one of the more significant problems and highlights the urgent need for alternatives to antibiotics [ 2 , 3 ]. Methicillin-resistant S. pseudintermedius and S. aureus (MRSA) cause most of the cutaneous infections in pets and can be transmitted to humans, with the number of zoonotic infections caused by these pathogens raising [ 14 , 15 ]. In particular, methicillin-resistant S. aureus is one of the most prevalent human and animal pathogens [ 15 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, methicillin-resistant S. aureus is one of the most prevalent human and animal pathogens [ 15 , 45 ]. Moreover, S. pseudintermedius causes the majority of skin infections in pets and can be also transmitted to humans as a zoonotic pathogen, with many of the isolates being methicillin resistant [ 11 , 12 , 13 , 14 , 46 , 47 ]. Moreover, the appearance of multiresistant strains and limitations on the use some antibiotics reserved for only human use due to precautionary principles sometimes makes the treatment of infections in animals challenging [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, MALDI-TOF can be a useful tool in screening cattle for the presence of the more hazardous clinically relevant version. Holmström et al [99] tackled the issue of prevalence of methicillin-resistant S. pseudintermedius in companion animals (dogs and cats). Isolates obtained from clinical samples were confirmed as isolates of S. pseudintermedius using MALDI-TOF.…”
Section: Streptococcus Salivarius Streptococcus Equinus Andmentioning
confidence: 99%